OVERVIEW OF THE MEDICAL RECORDS DEPARTMENT STAFF REQUIREMENT BASED ON HEALTHCARE WORKLOAD ANALYSIS METHOD AT UNIVERSITAS SEBELAS MARET HOSPITAL SUKOHARJO IN 2023 - Cahyaningrum, Nopita; Ika Wulandari, Fitria; Zaenal Abidin, Arif; Nur Afitri, Agita (LPPM Universitas Duta Bangsa Surakarta, 2023)
Universitas Sebelas Maret (UNS) Hospital currently employs 30 staff members in medical records department. The number of the staff exceeds the required workload. The objective of this research is to find out the requirement of medical records staff based on healthcare workload analysis method in UNS Hospital Sukoharjo. This research is a descriptive survey by implementing cross sectional approach. The samples taken are saturated samples. They are 30 staff members in medical records department. Data were collected through interviews and observations. The calculation of the requirement of medical records staff by implementing healthcare workload analysis method shows that 32 employees required in this department: 1 employee as a Head of Medical Records Deparment, 1 employee as a Registration Coordinator, 13 staff in Outpatient Services and Registration of Executive Patients and Online Patient, 4 employees in Emergency and Inpatient Services, 3 employees in Inpatient Assembly, and 4 employees in Outpatient Assembly and Inpatient/Outpatient Coding, and 6 employees in Medical Records Filing. In fact, there are currently 30 employees work in Medical Records Department of UNS Hospital, Sukoharjo. The result of healthcare workload analysis shows that this hospital needs 32 employees in this department. Therefore, it is suggested that the hospital should hire 2 more employees as staff members in Medical Records Department in order to effectively match the workload.